EVALUASI RASIONALITAS PENGGUNAAN ANTIBIOTIK ISPA PADA PASIEN RAWAT JALAN DI PUSKESMAS KECAMATAN GUNUNG SITOLI - Artha Yuliana Sianipar; Grace Anastasia Ginting; Yosefin Hellen (Universitas Haji Sumatera Utara, 2022)
URTI (Upper Respiratory Tract Infection) is a major disease in children in outpatient installation. Antibiotics are the most widely used class of drugs to treat infections. Antibiotics must be used rationally. Because the bad impact that occurs is the emergence of bacterial resistance. This study aims to obtain an overview of the rationality of the use of antibiotics in URTI patients, especially in children aged 5 to 11 years. The method used is a retrospective descriptive method, using medical record cards and prescription sheets for patients diagnosed with URTI and receiving antibiotics at the Gunungsitoli District Health Center during the period January to December 2020. Sampling used the purposive sampling method. Data that met the inclusion criteria were children aged 5-11 years and receiving antibiotic therapy. Then a table is made which includes the patient's identity, diagnosis, antibiotics, and the dose used. Then presented in the form of percentages, average values ​​and tables. The results showed that of the 64 patients who suffered the most URTI by age were patients aged 5 years (26.56%), the antibiotic group that was most often prescribed was the penicillin group, namely amoxicillin. (54.69%). Evaluation of rational use of antibiotics based on the 2011 Ministry of Health guidelines includes the right patient criteria (100%), right indication (100%), right frequency (100%), right drug (100%), right duration (98.44%), and right dose (93.75%).